Production of limit size nanoliposomal systems with potential utility as ultra-small drug delivery agents. (2nd April 2016) - Zhigaltsev, Igor V.; Tam, Ying K.; Leung, Alex K. K.; Cullis, Pieter R.
Abstract: Previous studies from this group have shown that limit size lipid-based systems – defined as the smallest achievable aggregates compatible with the packing properties of their molecular constituents – can be efficiently produced using rapid microfluidic mixing technique. In this work, it is shown that similar procedures can be employed for the production of homogeneously sized unilamellar vesicular systems of 30–40 nm size range. These vesicles can be remotely loaded with the protonable drug doxorubicin and exhibit adequate drug retention properties in vitro and in vivo . In particular, it is demonstrated that whereas sub-40 nm lipid nanoparticle (LNP) systems consisting entirely of long-chain saturated phosphatidylcholines cannot be produced, the presence of such lipids may have a beneficial effect on the retention properties of limit size systems consisting of mixed lipid components. Specifically, a 33-nm diameter doxorubicin-loaded LNP system composed of 1-palmitoyl-2-oleoyl phosphatidylcholine (POPC), 1, 2-dipalmitoyl phosphatidylcholine (DPPC), cholesterol, and PEGylated lipid (DSPE-PEG2000) demonstrated adequate, stable drug retention in the circulation, with a half-life for drug release of ∼12 h. These results indicate that microfluidic mixing is the technique of choice for the production of bilayer LNP systems with sizes less than 50 nm that could lead to development of a novel class of ultra-small drug delivery vehicles.